Revisiting the urban home: a critical approach - Gerhard, Ulrike; Malachuk, Daniel S. (Environment and planning. C, Politics and space, 2025)
We argue here for a more political concept of the home as the space that distinctively enables people to participate in public life by promoting civic orientations we call “resistance” and “yearning.” Because the political potential of home is most keenly experienced in cities, with their complex interplay of private and public spaces on very different scales (house, neighborhood, city), we present the urban home as a model for such politics. Our critical approach is in four parts. First, we reveal three patterns of thought in urban studies that lead scholars to examine housing while rendering the home an apolitical space. Second, we diagram how literary texts fruitfully challenge these patterns of thought in urban studies with their lavish attention to such specific home experiences. These literary descriptions suggest a fundamental politics of the urban home that we elaborate with the help of feminist recuperations of the home by Iris Marion Young, bell hooks, Doreen Massey and others. Third, we offer a more detailed empirical analysis of select texts associated with the “Great Migration” in the U.S. to illuminate this politics, particularly its fundamental orientations of resistance and yearning. To conclude, we propose an interdisciplinary agenda in urban studies that evades conceptual traps to politicize an otherwise neglected space: the urban home.
Gesehen am 13.03.2025
Online veröffentlicht: 24. November 2024